Developing Discovery-Based Flip E-Module to Support Undergraduate Students Collaboration - Muhimmatin, Ifa; Viclara, Dinicen; Jannah, Iis Ni’matul; Rahayu, Satutik (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
The implementation of discovery learning in plant systematics course requires learning media that can be used by undergraduate students. The learning media must have a user-friendly design and accessibility so that it can be used in the field. This study aims to develop a flip e-module as learning media in the discovery learning to enhance undergraduate students’ collaboration. This research is a Research and Development with 4D model with four stages: define, design, develop, and disseminate. The feasibility decision is based on various tests carried out including expert validation tests, readability tests, and classroom application tests by implementing flip e-module in discovery learning model. The results of expert validation and practicality tests indicate that the flip e-module is valid and no revision required. The results of the implementation test indicate that there is an increase in the quality of student collaboration with mean score from 75 to 84. The role of e-modules in discovery-based learning is to facilitate groupsâ€™ collaboration in carrying out the discovery activity stage. Further research in quasi-experimental design is needed to observe the effectiveness of e-modules.